Multisite assessment of aging-related tau astrogliopathy (ARTAG) - Kovacs, Gabor Geza; Schultz, Christian (Journal of neuropathology and experimental neurology, 2017)
Aging-related tau astrogliopathy (ARTAG) is a recently introduced terminology. To facilitate the consistent identification of ARTAG and to distinguish it from astroglial tau pathologies observed in the primary frontotemporal lobar degeneration tauopathies we evaluated how consistently neuropathologists recognize (1) different astroglial tau immunoreactivities, including those of ARTAG and those associated with primary tauopathies (Study 1); (2) ARTAG types (Study 2A); and (3) ARTAG severity (Study 2B). Microphotographs and scanned sections immunostained for phosphorylated tau (AT8) were made available for download and preview. Percentage of agreement and kappa values with 95% confidence interval (CI) were calculated for each evaluation. The overall agreement for Study 1 was >60% with a kappa value of 0.55 (95% CI 0.433-0.645). Moderate agreement (>90%, kappa 0.48, 95% CI 0.457-0.900) was reached in Study 2A for the identification of ARTAG pathology for each ARTAG subtype (kappa 0.37-0.72), whereas fair agreement (kappa 0.40, 95% CI 0.341-0.445) was reached for the evaluation of ARTAG severity. The overall assessment of ARTAG showed moderate agreement (kappa 0.60, 95% CI 0.534-0.653) among raters. Our study supports the application of the current harmonized evaluation strategy for ARTAG with a slight modification of the evaluation of its severity.